How will our Values Fit Future Work? An Empirical Exploration of Basic Values and Susceptibility to Automation. (3rd April 2021) - Långstedt, Johnny
ABSTRACT: The discussion of how automation, especially intelligent technologies such as artificial intelligence (AI), affects the workforce is a focal point in scholarship about the future of work. In contrast to previous technological advances, routine and structured knowledge work are believed to be substituted with intelligent technological solutions. The paper responds to a recent call for research on how the implementation of intelligent technologies will affect the work-values dimension of person-job fit. The discussion of future work has hitherto focused on how the technologies change skill requirements at work. However, as routine and structured work is substituted, the values with which the work fits change as well. To explore how intelligent technologies can affect the work-values fit, the paper draws data from the European Social Survey and analyses the relationship between occupational values and automatability in 126 occupations. The results indicate that person-job fit can decrease in automatable occupations if intelligent technologies are implemented in the way scholars expect.